The Efficiency of SNP-Based Microarrays in the Detection of Copy-Neutral Events at 15q11.2 and 11p15.5 Loci - Ozyilmaz, Berk; Kirbiyik, Ozgur; Ozdemir, Taha R.; Kaya, Ozge Ozer; Kutbay, Yasar B.; Erdogan, Kadri M.; Guvenc, Merve Saka; Koc, Altug (Journal of Pediatric Genetics, 2020)
Prader–Willi, Angelman, Beckwith–Wiedemann, and Russell–Silver are imprinting syndromes. In this study, we aimed to compare the efficiency of single nucleotide polymorphism (SNP) microarray analysis with methylation-specific Multiplex ligation-dependent probe amplification (MS-MLPA) in the detection of uniparental disomy in these syndromes. The patient samples with regions of loss of heterozygosity (LOH), covering 15q11.2 and 11p15.5 critical loci, were analyzed with MS-MLPA to demonstrate the efficiency of SNP microarray in the detection of uniparental disomy (UPD). In a total of seven patients, LOH covering 15q11.2 and 11p15.5 critical loci was detected. Two (28.6%) of these seven patients showed aberrant methylation (suggesting UPD) in MS-MLPA. SNP microarray is a useful tool in the detection of LOH; however, it should be used with caution, since false-positive or false-negative LOH results can be obtained. Although methylation analysis is recommended as the first tier test in the diagnosis of most of the imprinting disorders, combining methylation analysis with SNP microarray can enhance our evaluation process.
Keywords: SNP microarray; loss of heterozygosity; uniparental disomy